2023
DOI: 10.1038/s41523-022-00502-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of success in establishing orthotopic patient-derived xenograft models of triple negative breast cancer

Abstract: Patient-derived xenograft (PDX) models of breast cancer are an effective discovery platform and tool for preclinical pharmacologic testing and biomarker identification. We established orthotopic PDX models of triple negative breast cancer (TNBC) from the primary breast tumors of patients prior to and following neoadjuvant chemotherapy (NACT) while they were enrolled in the ARTEMIS trial (NCT02276443). Serial biopsies were obtained from patients prior to treatment (pre-NACT), from poorly responsive disease afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Additionally, the statistical analysis of the NAC group, which included TDLUP, Miller-Payne grade, and Ki-67LI in the multivariate logistic regression analysis, also demonstrated an excellent predictive ability with an AUC of 0.89. Compared to the PDX graft studies in the literature, our score was higher than that reported by Echeverria et al who incorporated two variables, Ki-67LI and metastatic LNs, into a logistic regression model for TNBCs breast PDX survival (AUC 0.70) [ 18 ]. In the same context, Zhuo et al [ 30 ] used GPC3 expression and KI67LI to predict hepatocellular carcinoma PDX engraftment and found a good discriminatory power (AUC 0.828), which is similar to the score obtained in the current study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Additionally, the statistical analysis of the NAC group, which included TDLUP, Miller-Payne grade, and Ki-67LI in the multivariate logistic regression analysis, also demonstrated an excellent predictive ability with an AUC of 0.89. Compared to the PDX graft studies in the literature, our score was higher than that reported by Echeverria et al who incorporated two variables, Ki-67LI and metastatic LNs, into a logistic regression model for TNBCs breast PDX survival (AUC 0.70) [ 18 ]. In the same context, Zhuo et al [ 30 ] used GPC3 expression and KI67LI to predict hepatocellular carcinoma PDX engraftment and found a good discriminatory power (AUC 0.828), which is similar to the score obtained in the current study.…”
Section: Discussionmentioning
confidence: 71%
“…In this study, high Ki-67LI, a cellular proliferation marker [ 16 18 ], emerged as a crucial factor for PDX engraftment. High histologic grade and TNBC subtype, often associated with elevated Ki-67LI, were consistently linked to increased PDX engraftment rates in prior studies [ 3 , 5 – 7 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As part of the prospective neoadjuvant ARTEMIS trial (NCT02276443) 13 15 , we obtained fine needle aspirates or core biopsies at critical clinical decision-making time points (Fig. 1 ) including clinical presentation before NACT (denoted as pre ), from residual tumors after four cycles of Adriamycin (doxorubicin) and cyclophosphamide (AC; timepoint denoted as mid ), and at surgical resection of residual tumors after paclitaxel ± targeted therapy (denoted as post ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have tried to determine predictive factors for engraftment success. Reported success has ranged between 23% and 75%, depending mostly on the tumor type and proliferation rate [18][19][20][21][22][23]. Overall, colorectal (64-89%) and pancreatic (62%) tumors have had high engraftment rates, but low-proliferation tumors such as receptor-positive breast cancers [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and neuroendocrine low-grade tumors have shown low success rates, even in the laboratories considered most successful in PDX engraftment in general [24].…”
Section: Introductionmentioning
confidence: 99%
“…Reported success has ranged between 23% and 75%, depending mostly on the tumor type and proliferation rate [18][19][20][21][22][23]. Overall, colorectal (64-89%) and pancreatic (62%) tumors have had high engraftment rates, but low-proliferation tumors such as receptor-positive breast cancers [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and neuroendocrine low-grade tumors have shown low success rates, even in the laboratories considered most successful in PDX engraftment in general [24]. Likewise, aggressive and advanced (metastatic) cancers have shown high PDX model success rates compared to less-aggressive and nonmetastatic cancers [18,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%